A Study on the Fine Eigenmodes in the Core Region of Coaxial Waveguide Induced by the Dielectric Cladding - Kim, Yeong Min (Transactions on Engineering and Computing Sciences, 2023)
The fine eigenmodes in the core region of the coaxial waveguide induced by the dielectric cladding are investigated by the finite element method. The relative permittivity of the core region is significantly higher than that of the cladding area. By appropriately adjusting the dielectric constant and geometry of the cladding, electromagnetic waves can be focused on the core region. When the eigenmode formed by the waveguide resonates with the electromagnetic wave, it can propagate long distances without seriously losing energy. In this study, eigenmodes localized in a fine core region are found using the numerical iteration method of the finite element method. As a result, TEM (Transverse Electro-Magnetic) eigenmodes are shown in a simple schematic representation. These results will enable the implementation of more advanced waveguides by utilizing the ideal characteristics of the cladding layer.